(untitled) (The Shivapuri Journal, 2024)
This article delves into the enduring relevance of the theories proposed by two renowned military thinkers for contemporary military professionals- Clausewitz and Sun Tzu, particularly to those at the mid-level officer ranks. Highlighting both shared and contrasting concepts, including war as an extension of policy, caution against prolonged conflicts, recognition of military genius, and appreciation of psychological factors, this article offers valuable insights for military practitioners in discerning and applying strategic principles in modern warfare. The paper explores the interplay between Clausewitz and Sun Tzu’s perspectives and further provides a nuanced understanding of their theories, aiding military leaders in navigating the complexities of today’s global security landscape.